2009
DOI: 10.1007/s12519-009-0053-y
|View full text |Cite
|
Sign up to set email alerts
|

Celiac disease in 87 children with typical and atypical symptoms in Black Sea region of Turkey

Abstract: Many children with celiac disease show an atypical form. The understanding of presentations of celiac disease may prevent delayed diagnosis. Celiac disease should be specially investigated in patients with recurrent iron deficiency anemia, short stature and autoimmune disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
28
3
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 26 publications
10
28
3
8
Order By: Relevance
“…Celiac disease is increasingly recognized in the Middle East and North Africa [3,[17][18][19][20], wherein it is becoming an increasing economic health burden [21]. The highest rate is reported in North Africa in Saharawi children [19].…”
Section: Epidemiologymentioning
confidence: 99%
“…Celiac disease is increasingly recognized in the Middle East and North Africa [3,[17][18][19][20], wherein it is becoming an increasing economic health burden [21]. The highest rate is reported in North Africa in Saharawi children [19].…”
Section: Epidemiologymentioning
confidence: 99%
“…Other studies [2831] reported a changing pattern in the presentation of pediatric CD towards more predominance of atypical presentations of CD and older age at diagnosis. …”
Section: Discussionmentioning
confidence: 97%
“…Ülkemizde çölyak hastalarının başvuru esnasındaki bulgularını araştıran az sayıda çalışma bulunmaktadır (9)(10)(11). Özellikle son iki dekatta yapılan ulusal ve uluslar arası çalışmalarda da çölyak hastalarının yaş ortalamasının arttığı ve Bu çalışmada, çölyak hastalığına eşlik ettiği bilinen klasik hastalıklara ek olarak 3 hastada obesite saptandı.…”
Section: Discussionunclassified
“…Hastalığın başlangıç yaşı, mukozal hasarın şiddeti, diyet alışkanlığı ve cinsiyetin klinik farklılıklardan sorumlu olabileceği belirtilmektedir (8). Türk çocuklarında çölyak hastalığının başvuru bulgularını inceleyen üç adet çalışma bulunmaktadır (9)(10)(11). Bu çalışmada da merkezimizde çölyak tanısı alan ve izlenmekte olan hastaların başvuru bulguları incelenmiştir.…”
Section: Introductionunclassified